(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The object of this study is to assess the removal of Fe(III) ions from aqueous solutions onto modified chitosan. The effect of various parameters has been investigated by the following batch adsorption technique. The various variables studied include initial concentration of the adsorbate, agitation time, adsorbent dosage, kinetics, influence of temperature. The experimental data was fit well to the Freundlich isotherm. Thermodynamic parameters such as Î”H, Î”S and Î”G were calculated, indicating that the adsorption was spontaneous and endothermic nature.